Comparative optical and radiocarbon dating of laminated Holocene sediments in two maar lakes : Lake Keilambete and Lake Gnotuk, south-western Victoria, Australia - Wilkins, Daniel. (2013)
Sediment core chronologies of optical dates on single-grains/very small aliquots of sand-sized quartz are compared with Accelerator Mass Spectrometry (AMS) radiocarbon (14C) chronologies from ostracod carbonate, mixed carbonates, sedimentary organic matter and charcoal in order to establish the age of laminated Holocene sediments in maar crater lakes Keilambete and Gnotuk, Victoria, Australia. Samples for optical and AMS 14C dating were taken from the same Mackereth cores, allowing a direct comparison of the two techniques from two laminated sedimentary sequences. Additional AMS 14C samples were taken from water in Lake Keilambete and from groundwater discharging into Lake Keilambete from the crater wall, with equivalent reservoir ages of 150 ± 30 and 1940 ± 30 years respectively. AMS 14C dating of modern ostracod carbonate in Lake Keilambete demonstrates a reservoir age of 670 ± 175 years. Optical dating of ‘single-grain/very small aliquots’ of sand-sized-quartz indicate the presence of a radiocarbon reservoir in Lake Keilambete that is consistent with that measured on modern ostracods, and also demonstrate that there is no 14C reservoir in Lake Gnotuk during the Holocene. The chronology presented here supports the premise that previously published bulk conventional 14C dates from Lake Keilambete were affected by old carbon, meaning that past chronologies require revision. Limitations on the use of optical dating of single-grain/very small aliquots include the relative paucity of sand-sized quartz, which decreases the precision of the sample equivalent dose (De), and is further confounded by low environmental dose rates and resultant large uncertainties on the final age assessment. Nevertheless, evidence for partial bleaching confirms that single-grain quartz dating is the most appropriate luminescence technique, and may prove a useful alternative in situations where 14C dating is unsuitable or an alternative chronometer is required.